Analysis of the Intent to Use QRIS Continuously by MSME Actors in North Sumatra - Zulfahmi Syahputra Nasution; Arsy Annisa Asti (CV Pena Jaya Pers, 2026)
The digitization of payment systems is an important pillar in accelerating global financial inclusion. In Indonesia, the implementation of the Indonesian Standard QR Code (QRIS) by Bank Indonesia has accelerated the use of cashless payments, particularly in the Micro, Small, and Medium Enterprises (MSME) sector. Although the initial adoption rate has increased rapidly, the main challenge lies in the continuance intention of micro-businesses, which are more sensitive to costs, risks, and business margins than other business segments. Previous studies have emphasized the initial adoption aspect, so that retention factors in micro MSMEs have not been explored in depth. This study develops an integrative model that combines Expectancy Theory and the variable of Trust to explain the intention to use QRIS sustainably among micro businesses. Expectancy Theory is used to capture rational motivation based on perceived value and expected outcomes, while Trust is included as a crucial factor given the high perception of digital transaction risk in the micro business segment. This study aims to examine the structural relationship between business expectations, valence, instrumentality, trust, and the intention to continue using QRIS. The research results are expected to contribute to the development of theory through the formulation of a more contextual technology acceptance model for micro-businesses. In practical terms, the findings of this study provide strategic recommendations for regulators and Payment Service Providers (PSPs) in designing interventions to increase the retention and sustainable use of QRIS in the micro-business sector.